Saving free trade : a pragmatic approach - Lawrence, Robert Z.; Litan, Robert E. (Washington, D.C. : Brookings Institution, 1986)
The book focuses on the escape clause of the U.S. Trade Act of 1974, meant to provide domestic industries temporary shelter from severe import competition, and the trade adjustment assistance program, designed to provide direct aid to companies, workers, and communities injured by imports.
Includes bibliographical references and index.
osc 08/06/2018
Loans
Keywords: Trade adjustment assistance; Free trade; United States